Evaluation of niobium carbide coatings produced on AISI L2 steel via thermo-reactive diffusion technique. (December 2017) - Soltani, Reza; Sohi, Mahmoud Heydarzadeh; Ansari, Mohammad; Haghighi, Ahmadreza; Ghasemi, Hamid M.; Haftlang, Farahnaz
Abstract: Thermo-reactive diffusion (TRD) is a high-temperature process for producing hard metal carbide coatings on carbon-containing substrates. In this study, niobium carbide (NbC) coatings were produced on low-alloy special-purpose tool steel (AISI L2) via a thermo-reactive powder-pack treatment. The treatment was done in a sealed box with a powder mixture consisted of ferroniobium, ammonium chloride and alumina powders at different times and temperatures. The ratio of the powders was optimized based on the thickness of coatings. The presence of NbC was confirmed by XRD and the growth kinetics of the coatings was studied, as well; leading to an empirical equation to estimate the thickness of coating based on treatment time and temperature. Moreover, pin-on-disc wear tests were conducted on the coatings at various applied loads. The results showed a significantly higher wear resistance and lower coefficient of friction for the coated metal compared to the bare metal. Highlights: NbC coatings were produced on AISI L2 steel via powder-pack TRD process. The process was optimized and the growth kinetics was investigated experimentally. Wear behavior was investigated and wear mechanisms were elucidated.